A preliminary study of the novel antibiotic-loaded cement computer-aided design-articulating spacer for the treatment of periprosthetic knee infection - Chun-Hao Tsai; Horng-Chaung Hsu; Hui-Yi Chen; Yi-Chin Fong; Mao-Wang Ho; Chia-Huei Chou; Yi-Wen Chen; Ming-You Shie; Tsung-Li Lin (Journal of Orthopaedic Surgery and Research, 2019)
Abstract Background In comparison to static spacers, articulating spacers have been shown to result in a similar infection eradication rate in two-stage revision of periprosthetic knee infections. However, the optimal construct for articulating spacers has not been identified yet. The aim of this study was to present a preliminary result of treatment for periprosthetic knee infection using a novel computer-aided design (CAD)-articulating spacer. Methods We retrospectively reviewed 32 consecutive cases of chronic periprosthetic knee infection occurring from January 2015 to December 2015. In these cases, we used an antibiotic-loaded, optimized CAD-articulating spacer based on the retrieved knee prosthesis. Evaluation included infection eradication rate, the Hospital of Special Surgery (HSS) knee score, range of motion (ROM), and spacer-related mechanical complications. All cases were regularly followed-up for 2 years minimum. Results Twenty-eight of 32 patients (87.5%) had infection eradication; 18 patients (56.3%) received reimplantation successfully. The mean interval between spacer insertion and reimplantation was 8.8 months (range 4.0–12.5 months). The mean HSS knee score and ROM significantly increased during each interval (p < 0.0001 for both). The mean HSS knee scores were 31.2 (range 20–48) at initial visit, 65.4 (range 60–78.8) at 1 month after spacer insertion, and 84.2 (range 78–90) at 3 months after reimplantation (p < 0.0001). The mean ROM were 72.0° (range 15–100°), 85.6° (range 35–110°), and 102.0° (range 80–122°), respectively (p = 0.002). Two (6.3%) spacer-related mechanical complications occurred. Conclusions The CAD-articulating spacer in two-staged revision of periprosthetic knee infection significantly controlled infection, improved clinical outcomes, increased ROM, and decreased mechanical complications in the preliminary study. Further larger clinical studies are needed to confirm the findings presented here.